Phase II Study of Lenalidomide and Rituximab As Salvage Therapy for Patients With Relapsed or Refractory Chronic Lymphocytic Leukemia - Badoux, Xavier C. (J Clin Oncol, 2013)
PURPOSE: Lenalidomide is an immunomodulatory drug active as salvage therapy for chronic lymphocytic leukemia (CLL). We combined lenalidomide with rituximab to improve response rates in patients with relapsed or refractory CLL. PATIENTS AND METHODS: Fifty-nine adult patients (age 42 to 82 years) with relapsed or refractory CLL were enrolled onto a phase II study of lenalidomide and rituximab. Patients had received prior fludarabine-based therapy or chemoimmunotherapy. Rituximab (375 mg/m(2) intravenously) was administered weekly during cycle one and on day 1 of cycles three to 12. Lenalidomide was started on day 9 of cycle one at 10 mg orally and administered daily continuously. Each cycle was 28 days. Rituximab was administered for 12 cycles; lenalidomide could continue indefinitely if patients benefitted clinically. RESULTS: The overall response rate was 66%, including 12% complete responses and 12% nodular partial remissions. Time to treatment failure was 17.4 months. Median overall survival has not been reached; estimated survival at 36 months is 71%. The most common grade 3 or 4 toxicity was neutropenia (73% of patients). Fourteen patients (24%) experienced a grade 3 to 4 infection or febrile episode. There was one episode of grade 3 tumor lysis; one patient experienced renal failure during the first cycle of therapy, and one venous thromboembolic event occurred during the study. CONCLUSION: The combination of lenalidomide and rituximab is active in patients with recurrent CLL and warrants further investigation.